Polyimide varnish with improved pulse durability and polyimide coating material prepared therefrom
By adding nanosilicon dioxide to the polyimide varnish and controlling its zeta potential, the problem of pulsed durability of the polyimide coating material under high voltage conditions is solved, achieving excellent durability and low haze.
Patent Information
- Application Number
- CN202411186701.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-28
- Filing Date
- 2024-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
Under high voltage conditions, polyimide coating materials are prone to partial discharge, resulting in insulation breakdown and shortened service life, and the prior art is difficult to effectively improve its pulse durability.
The pulse durability and haze are improved by adding nanosilicon dioxide in a certain range of content to the polyimide varnish and controlling its absolute value of zeta potential.
The excellent pulse durability and low haze of polyimide coating materials are achieved, extending the service life of electrical equipment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority under 35 U.S.C. §119 to Korean Patent Application No. 10-2023-0112846 filed on August 28, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The following disclosure relates to a polyimide varnish and a polyimide coating material prepared therefrom, and particularly to a polyimide varnish having excellent pulse durability and a polyimide coating material prepared therefrom. Background Art
[0004] Polyimide resin refers to a high heat-resistant resin obtained by solution polymerization of aromatic dianhydride and aromatic diamine or aromatic diisocyanate to generate a polyamic acid derivative, followed by closed-loop dehydration and imidization at high temperature. Polyimide resin is an insoluble, refractory, ultra-high heat-resistant resin with excellent properties such as thermal oxidation resistance, heat resistance, radiation resistance, low temperature characteristics, and chemical resistance. Therefore, it is used in a wide range of fields, including heat-resistant advanced materials such as automotive materials, aviation materials, and spacecraft materials, as well as electronic materials such as insulating coatings, insulating films, semiconductors, and electrode protection films for TFT-LCDs. Recently, polyimide resins have also been used in display materials such as optical fibers and liquid crystal alignment films, transparent electrode films, etc. by containing conductive fillers in the film or performing surface coating.
[0005] In particular, in insulated wires used as coil windings of motors, etc., the insulating layer (insulating film) covering the conductor is required to have excellent insulation properties, adhesion to the conductor, heat resistance, mechanical strength, etc. Therefore, polyimide is used as a resin to form the insulating layer.
[0006] However, in electrical equipment with high applied voltage, such as motors used at high voltage, in insulating layer or coating materials, high voltage is applied to insulated wires constituting the electrical equipment, polyimide having excellent pulse withstand characteristics capable of withstanding such high voltage has yet to be developed.
[0007] Specifically, local discharge (corona discharge) is prone to occur on the coating surface where high voltage is applied. When corona discharge occurs, causing local temperature rise or generating ozone or ions, the coating of the insulated wire may deteriorate, resulting in premature insulation breakdown and shortening the service life of the electrical equipment. Therefore, when using polyimide as a coating material for conductors, especially as a coating material when high voltage is applied, it is necessary to improve pulse endurance characteristics such as insulation breakdown voltage performance or corona discharge initiation voltage. Summary of the invention
[0008] One embodiment of the present invention is directed to providing a polyimide varnish, which comprises nano-silicon dioxide within a certain content range, wherein the polyimide varnish has a higher absolute value of zeta (ζ) potential.
[0009] Another embodiment of the present invention is directed to providing a polyimide varnish having excellent physical properties such as pulse durability and haze.
[0010] Yet another embodiment of the present invention is directed to providing a polyimide cured product in which a polyimide varnish is cured.
[0011] Yet another embodiment of the present invention is directed to providing a polyimide coating material comprising a polyimide varnish.
[0012] Various modifications can be made in the present invention, and various embodiments can be implemented. However, these embodiments are not intended to limit the present invention to specific embodiments, but should be understood to include all modifications, equivalents and substitutes within the spirit and scope of the present invention.
[0013] The terms used in this application are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, singular expressions include plural expressions. In this specification, terms such as "comprising" or "having" are intended to specify the presence of features, quantities, steps, operations, elements, parts, or combinations thereof described in this specification, and should not be understood as excluding the possibility of existing or increasing one or more other features, quantities, steps, operations, elements, parts, or combinations thereof.
[0014] When amounts, concentrations or other values or parameters are given herein in the form of ranges, preferred ranges or lists of desirable upper values and desirable lower values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether the range is disclosed individually.
[0015] Where a numerical range is described herein, it is intended that the endpoints of the range and the parent invention within the range are not limited to the specific values described when defining the range, unless otherwise indicated.
[0016] As used herein, "dianhydride" is intended to include its precursors or derivatives, which are also referred to as "dianhydrides" or "acid dianhydrides." These products may not technically be dianhydrides, but can still react with diamines to form polyamic acids, which in turn can be converted back to polyimides.
[0017] As used herein, "diamine" is intended to include precursors or derivatives thereof which may not technically be diamines but can still react with a dianhydride acid to form a polyamic acid which in turn can be converted back to a polyimide.
[0018] In addition, unless otherwise defined, all terms used herein, including technical or scientific terms, are the same as those commonly understood by those of ordinary skill in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning in the context of the relevant field, and should not be interpreted in an idealized or overly formalized manner unless clearly defined in this application. The specific details of implementing the present invention will be described below.
[0019] Polyimide varnish
[0020] In one general aspect, polyimide varnishes are provided having improved pulse durability useful for conductor coatings.
[0021] In one aspect of the present invention, a polyimide varnish is provided, comprising: polyamic acid and nano-silicon dioxide, wherein the content of the nano-silicon dioxide is 5 to 23 wt % relative to the solid content of the polyamic acid, and the absolute value of the zeta potential of the polyimide varnish is 1 to 30 mV.
[0022] Here, zeta potential is the potential difference of colloidal particles suspended in a liquid phase. Particles dispersed in a solution have negative (-) or positive (+) charges on their surfaces, and the concentration of (+) ions increases around the (-) charged colloidal particles, forming a Stern layer. Outside the Stern layer is a diffusion layer, which reduces the concentration of (+) ions, thereby achieving a balance between (-) ions and (+) ions. The potential difference between the starting point of the diffusion layer and the equilibrium point of (-) ions and (+) ions is called the zeta potential. This zeta potential can be used as a measure of the stability of a dispersed sol because it reflects the strength of the repulsive force between charged particles in the dispersion. Whether it is negative (-) or positive (+), the higher the value of the zeta potential, the stronger the electrical repulsion between the particles, so the distance between the particles increases, thereby achieving a stable state without agglomeration. The zeta potential value can be used to determine the measure of dispersion stability. In other words, the larger the absolute value of the zeta potential, the better the dispersion. Furthermore, different solvents, concentrations, pH, functional groups, and surface properties of the particles may result in different zeta potential values, making it desirable to use zeta potential for comparison as a measure of stability.
[0023] Nano Silica
[0024] The polyimide varnish of the present invention may contain inorganic particles to improve physical properties such as pulse durability, wherein the inorganic particles are nano-silica, i.e., nano-scale silica (SiO2) fine particles having an average particle diameter of 1000nm or less, and their form and shape are not particularly limited.
[0025] In addition, the amount of nano-silica can be 5 to 23wt% relative to the solid content of polyamic acid. For example, the lower limit of the amount of nano-silica can be 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt% or 11.0wt% or more. In addition, the upper limit of the amount of nano-silica can be 22.0wt%, 21.5wt%, 21.0wt%, 20.5wt%, 20.0wt%, 19.0wt%, 18.5wt%, 18.0wt%, 17.0wt%, 16.0wt%, 15.0wt%, 14.0wt%, 13.5wt% or 13.0wt% or less. When the amount of nano-silica is less than 5wt%, it is ineffective to improve pulse durability; when the amount of nano-silica exceeds 23wt%, it is undesirable because physical properties may be reduced. Here, the solid content of the polyamic acid is the total amount of the dianhydride monomer and the diamine monomer used in the polymerization reaction.
[0026] The absolute value of the zeta potential of nano-silicon dioxide can be 10.0 mV to 40.0 mV. For example, the lower limit of the absolute value of the zeta potential of nano-silicon dioxide can be 10.5 mV or higher, 11.0 mV or higher, 11.5 mV or higher, 12.0 mV or higher, 12.5 mV or higher, 13.0 mV or higher, 13.5 mV or higher, 14.0 mV or higher, 14.5 mV or higher, 15.0 mV, 16.0 mV or 17.0 mV or higher, and the upper limit can be 38.0 mV or lower, 39.0 mV or lower, 40.0 mV or higher, 41.0 mV or higher, 43.0 mV or higher, 44.0 mV or higher, 45.0 mV or higher, 46.0 mV or higher, 47.0 mV or higher, 48.0 mV or higher, 49.0 mV or higher, 50.0 mV or higher, 51.0 mV or higher, 52.0 mV or higher, 53.0 mV or higher, 54.0 mV or higher, 55.0 mV or higher, 56.0 mV or higher, 57.0 mV or higher, 58.0 mV or higher, 59.0 mV or higher, 60.0 mV or higher, 61.0 mV or higher, 62.0 mV or higher, 64.0 mV or higher, 65.0 mV or higher, 66.0 mV or higher, 67.0 mV or higher, 68.0 mV or higher, 69.0 mV or higher, 71.0 mV or higher, 73.0 mV or higher, 74.0 mV or higher, 7 0mV or lower.5.0mV or lower, 32.0mV or lower, 30.0mV or lower, 28.0mV or lower, 27.0mV or lower, 26.0mV or lower, 25.0mV or lower, 24.0mV or lower, 23.5mV or lower, 23.0mV or lower, 22.5mV or lower, 22.0mV or lower, 21.0mV or lower, 20.0mV or lower, 19.0mV or 18.0mV or lower.By controlling the absolute value range of the zeta potential of nano silicon dioxide, the high dispersibility of nano silicon dioxide in polyimide varnish can be kept without flocculation, thereby improving pulse durability (corona resistance).Here, zeta potential can be the zeta potential of nano silicon dioxide (silica sol) dispersed in an organic solvent, and the pH of silica sol can be 2 to 12.
[0027] In an example, the zeta potential of nano-silica dispersed in an organic solvent can be measured by inputting the refractive index, viscosity and dielectric constant of the organic solvent (dispersion medium) into Benano 180 Zeta Pro manufactured by Bettersize instruments Ltd. The organic solvent can be any one selected from the group consisting of: N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), dimethylacetamide (DMAc), dimethylformamide (DMF) and diethylformamide (DEF).
[0028] For example, at 25°C, the organic solvent may have a refractive index of 1.2 to 1.6, a viscosity of 0.5 cP to 2.0 cP, and a dielectric constant of 30 to 40. Preferably, for example, at 25°C, the organic solvent may have a refractive index of 1.3 to 1.5, a viscosity of 0.7 cP to 1.7 cP, and a dielectric constant of 32 to 39, more preferably, at 25°C, the refractive index is 1.35 to 1.47, the viscosity is 0.8 cP to 1.0 cP, and the dielectric constant is 35 to 38.5, more preferably, at 25°C, the refractive index is 1.4 to 1.45, the viscosity is 0.85 cP to 0.95 cP, and the dielectric constant is 37 to 38.
[0029] In an example, nano-silica dispersed in dimethylacetamide may be used (here, the solid content concentration of silica is 30 wt %).
[0030] In addition, the average particle diameter of nano-silicon dioxide can be 1 to 200 nm, specifically, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm or 10 to 30 nm. The average particle diameter can be measured by BET, SEM, zeta potential analyzer and other equipment.
[0031] The nano-silica may also be nano-silica surface-modified with organic silane.
[0032] The organosilane of the nano-silica surface-modified with the organosilane may include one or more selected from the group consisting of methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styreneethyltrimethoxysilane, phenyltriethoxysilane, Oxysilane, triethoxy p-toluenesilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltrimethoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropoxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidyl ether propyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxysilane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).
[0033] In addition, the nano-silica surface-modified with organosilane can be obtained by combining the compound containing at least one phenyl at the end and the compound containing at least one amine group, hydroxyl group, thiol group or epoxy group at the end on the surface of nano-silica. Specifically, the compound containing at least one phenyl at the end can be phenyltrimethoxysilane (PTMS) or N-phenyl-3-aminopropyltrimethoxysilane (PAPTES). In addition, the compound containing at least one amine group, hydroxyl group, thiol group or epoxy group at the end can be glycidyl ether propyltrimethoxysilane (GPTMS) or 3-aminopropyltrimethoxysilane (APTMS).
[0034] Nano-silica surface-modified with organosilane can be prepared by surface-treating nano-silica with organosilane. For example, nano-silica can be obtained by heating organosilane under acidic or alkaline conditions and performing surface treatment for about 1 to 24 hours. In addition, surface modification can also be achieved by other known methods, for example, surface-modified nano-silica can be obtained by mixing organosilane in a solvent and reacting at a temperature of 10 to 100° C. or 20 to 60° C. for 1 to 10 hours or 1 to 5 hours. In order to combine two or more compounds on the surface of nano-silica, each of the above methods can be performed.
[0035] The nano-silica surface-modified with the organosilane of the present invention can prevent the inorganic particles in the polyimide varnish from agglomerating, and can enhance the interaction with the solid component (polyamic acid) due to the functional groups of the compound, thereby improving the dispersibility and miscibility.
[0036] Polyamic acid
[0037] In the present invention, the polyamic acid may include a dianhydride monomer and a diamine monomer as polymerization units.
[0038] The dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenyl sulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimer monoester anhydride), p-biphenylenebis(trimer monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.
[0039] Specifically, the dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), and benzophenonetetracarboxylic dianhydride (BTDA), and more preferably pyromellitic dianhydride (PMDA).
[0040] In addition, the diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenylpropane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-toluidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3 '-Dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl) sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-diamino Chlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl) )benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]thioether, bis[4-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(3-aminophenoxy)phenyl]sulfone , bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane , 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.
[0041] Specifically, the diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenylpropane (BAPP) and 1,3-bis(4-aminophenoxy)benzene (TPE-R), and preferably may include 4,4'-diaminodiphenyl ether (ODA).
[0042] The polyamic acid may contain pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as polymerization units.
[0043] In the present invention, in all the dianhydride monomers, pyromellitic dianhydride (PMDA) may be included in a ratio of 50 mol % or more, specifically 60 mol % or more, 70 mol % or more, 75 mol % or more, 80 mol % or more, 85 mol % or more, 90 mol % or more, 95 mol % or more, 99 mol % or more, or 100 mol % or more.
[0044] In addition, in the whole diamine monomers, 4,4'-diaminodiphenyl ether (ODA) may be included in a ratio of 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.
[0045] Polyamic acid of the present invention can contain 95 to 105mol% dianhydride monomer (based on 100mol% diamine monomer).For example, the lower limit of dianhydride monomer can be 96mol% or more, 97mol% or more, 98mol% or more, 99mol% or more, or 99.5mol% or more, and its upper limit can be 104mol% or less, 103mol% or less, 102mol% or less, 101mol% or less, or 100.5mol% or less.In one embodiment, diamine monomer and dianhydride monomer can react with basic equimolar amount.
[0046] In addition, the molar ratio of the dianhydride monomer to the diamine monomer may be 6:4 to 4:6, preferably 5.5:4.5 to 4.5:6.5, and more preferably 5:5.
[0047] In addition, the solid content of polyamic acid can be 10 to 50wt%. The lower limit of the solid content of polyamic acid can be, for example, 13wt% or more, 15wt% or more, 18wt% or more, 20wt% or more, 23wt% or more, or 24wt% or more, and its upper limit can be, for example, 48wt% or less, 45wt% or less, 43wt% or less, 40wt% or less, 38wt% or less, 35wt% or less, 33wt% or less, 30wt% or less, or 27wt% or less. By adjusting the solid content of polyamic acid, the increase of viscosity can be controlled and the processing time in the curing process can be shortened.
[0048] Organic solvents
[0049] In the present invention, the polyimide varnish further contains an organic solvent, wherein the organic solvent is not particularly limited as long as it is an organic solvent in which the polyamic acid is soluble, but as an example, may be an aprotic polar solvent.
[0050] Specifically, the organic solvent may include at least one selected from the group consisting of: N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, gamma-butyrolactone (GBL), diethylene glycol dimethyl ether and naphthalene. Preferably, the organic solvent may be N-methylpyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), etc.
[0051] The organic solvent may further include a modifier containing a hydroxyl group (OH) or an amine group (NH). Examples of modifiers containing a hydroxyl group (OH) or an amine group (NH) may include ethylamine, triethanolamine, dimethylamine, trimethylamine, diethylenetriamine, ethylenediamine, tributylamine, pyridine, pyrrolidine, methanol, ethanol, propanol, isopropanol, sec-butyl alcohol, tert-butyl alcohol, n-pentanol, isopentanol, hexanol, octanol, octyl alcohol, nonyl alcohol, decyl alcohol, undecyl alcohol, lauryl alcohol, myristyl alcohol, hexadecyl alcohol, stearyl alcohol, allyl alcohol, crotyl alcohol, propargyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, phenol, etc. The modifier may control reactivity by reacting with the dianhydride monomer.
[0052] Polyimide varnish
[0053] In the present invention, the absolute value of the zeta potential of the polyimide varnish may be 1 to 30 mV. For example, the lower limit of the absolute value of the zeta potential of the polyimide varnish may be 1.5 mV or more, 2.0 mV or more, 3 mV or more, 4 mV or more, 4.3 mV or more, 5.0 mV or more, 6.0 mV or more, 6.5 mV or more, 7.0 mV or more, 8.0 mV or more, 8.5 mV or more, or 9.0 mV or more, and the upper limit thereof may be 29.5 mV or less, 29.0 mV or less, 28.5 mV or less. .0 mV or less, 27.0 mV or less, 26.0 mV or less, 25.0 mV or less, 24.0 mV or less, 23.0 mV or less, 22.0 mV or less, 21.5 mV or less, 21.0 mV or less, 20.0 mV or less, 19.0 mV or less, 18.0 mV or less, 17.0 mV or less, 16.0 mV or less, 15.0 mV or less, or 14.0 mV or less.
[0054] As at a temperature of 30°C and 1s -1 The viscosity of the polyimide varnish may be 500 cP to 20,000 cP measured at a shear rate of . For example, the upper limit of the viscosity may be 20,000 cP, 15,000 cP, or 10,000 cP or lower. The lower limit of the viscosity is not particularly limited, but may be 1,000 cP, 1,200 cP, 1,500 cP, or 1,800 cP or higher. The viscosity may be measured using, for example, Haake's Rheostress 600, and may be measured at a shear rate of 1 / s, a temperature of 30 ° C, and a plate gap of 1 mm. The present invention can provide a polyimide varnish having excellent processing properties by adjusting the viscosity range.
[0055] The haze of polyimide varnish can be 1.5% or lower. For example, the upper limit of the haze can be 1.4% or lower, 1.3% or lower, 1.2% or lower, 1.1% or lower, 1% or lower, 0.9% or lower, or 0.8% or lower, and its lower limit is not particularly limited, but can be greater than 0%, 0.05% or higher, or 0.1% or higher. In one embodiment, the haze can be measured using HunterLab equipment according to ASTM E308 standard.
[0056] In addition, the present invention can prevent nano-silica from agglomerating in the polyimide varnish, and by containing a certain range of high content of nano-silica and maintaining the absolute value of the zeta potential of the polyimide varnish at a high level, the polyimide varnish has excellent dispersibility, thereby achieving a low level of haze.
[0057] Polyimide varnish curing products and coating materials
[0058] In another aspect of the present invention, there is provided a polyimide cured product obtained by curing the above-mentioned polyimide varnish, wherein the polyimide cured product may be a polyimide film.
[0059] The haze of the polyimide cured product can be 1.5% or less. For example, the upper limit of the haze can be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less, and its lower limit is not particularly limited, but can be greater than 0%, 0.05% or more, or 0.1% or more. In one embodiment, the haze can be measured using HunterLab equipment according to ASTM E308, wherein the thickness of the polyimide cured product is 20 ± 1.0 μm.
[0060] The polyimide cured product can have a pulse durability of 300 minutes or longer, and according to IEC-60851-5, pulse durability is the time that an insulating material withstands a certain voltage. The lower limit of pulse durability can be, for example, 400 minutes or longer, 500 minutes or longer, 550 minutes or longer, 600 minutes or longer, 650 minutes or longer, 700 minutes or longer, 750 minutes or longer, 800 minutes or longer, 850 minutes or longer, 900 minutes or longer, 950 minutes or longer, 970 minutes or longer, 980 minutes or longer, 1000 minutes or longer, 1100 minutes or longer, 1200 minutes or longer, 1300 minutes or longer, 1400 minutes or longer, 1500 minutes or longer, or 2000 minutes or longer. Its upper limit is not particularly limited, but can be 4000 minutes or shorter. The pulse durability can be determined by attaching the polyimide coating material to a jig, applying a 1.5 kV AC voltage (at a frequency of 60 Hz), and measuring the time until a leakage current of 5 mA or more is detected. Here, the thickness of the polyimide cured product can be 26 ± 1.0 μm.
[0061] Furthermore, according to the present invention, the pulse endurance characteristics can be improved by containing a high content of nano-silica within a certain range and maintaining the absolute value of the zeta potential of the polyimide varnish at a high level.
[0062] In still another aspect of the present invention, a polyimide coating material including a polyimide cured product is provided.
[0063] In one embodiment, a method of preparing a polyimide coating material may include coating a polyimide varnish on a surface of a conductor; and imidizing the polyimide varnish coated on the surface of the conductor.
[0064] The conductor may be a copper wire made of copper or a copper alloy, but may also include a conductor made of other metal materials, such as a silver wire, etc., or various metal-plated wires, such as an aluminum-plated wire or a tin-plated wire, etc. The conductor and the coating material may have a thickness that conforms to the KS C3107 standard. The diameter of the conductor may be in the range of 0.3 to 3.2 mm, and the standard film thickness of the coating film (the average value of the maximum film thickness and the minimum film thickness) may be: 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. According to the cross-sectional shape of the conductor, the conductor may have a circular, rectangular, hexagonal, etc. shape, but is not limited thereto.
[0065] In another aspect of the present invention, an electrical wire comprising a polyimide coating material is provided.
[0066] Specifically, the conductor may be a coated conductor comprising a polyimide coating material, which is prepared by coating a polyimide varnish on the conductor surface and then performing imidization. In one embodiment, the coated conductor may comprise an electric wire; and a coating material, wherein the polyimide is coated on the conductor surface and imidized.
[0067] In addition, the present invention can also provide an electronic device comprising a coated wire. For example, the electronic device can be a motor.
[0068] Furthermore, in another aspect, the present invention also provides a component including a molded body formed of the polyimide varnish.
[0069] Specifically, the components may include electronic circuit board components, semiconductor devices, lithium-ion battery components, solar cell components, fuel cell components, motor windings, engine peripheral components, coatings, optical components, thermal insulation materials, electromagnetic shielding materials, surge components, dental materials, sliding coatings, and electrostatic chucks. DETAILED DESCRIPTION
[0070] To facilitate understanding of the present disclosure, the following examples are provided. These examples are provided only to make it easier to understand the present disclosure, but the content of the present disclosure is not limited to these examples.
[0071] <Example>
[0072] Preparation Example 1: Nano-silicon dioxide surface treated with organosilane
[0073] Nano-silica 1 treated with organosilane surface (silica sol dispersed in dimethylacetamide, silica solid content concentration of 30wt%, silica average particle diameter of 10-30nm, average zeta potential (absolute value) of 17.86mV) was prepared. Here, the zeta potential is determined by inputting the refractive index, viscosity and dielectric constant of dimethylacetamide into the Benano180 zeta pro instrument of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0074] Preparation Comparative Example 1. Nano-silicon dioxide
[0075] Nano-silica (silica sol dispersed in N-methylpyrrolidone, silica solid content concentration of 30 wt%, silica average particle diameter of 10-20 nm, average zeta potential (absolute value) of 8.42 mV) was prepared. Here, the zeta potential was determined by inputting the refractive index, viscosity and dielectric constant of N-methylpyrrolidone into the Benano180 zeta pro instrument of Bettersize, performing repeated measurements, and then calculating the arithmetic mean.
[0076] Example 1. Polyimide varnish
[0077] Example 1-1
[0078] In a reaction vessel filled with nitrogen, an organic solvent containing dimethylacetamide (DMAc) and a modifier (0-2 mol%) was added, and the nano-silica surface-treated with an organosilane (6 wt% relative to the polyimide solid content) according to Preparation Example 1 and pyromellitic anhydride (PMDA) (92 mol%) as a dianhydride monomer were mixed and stirred at 40° C. for 30 minutes. Then, 4,4'-diaminodiphenyl ether (ODA) (100 mol%) and pyromellitic anhydride (PMDA) (8 mol%) were added as diamine monomers, and the mixture was stirred and polymerized at 40° C. for about 1 hour to prepare a polyimide varnish (25 wt% polyimide solid content).
[0079] Examples 1-2 to 1-7
[0080] A polyimide varnish was prepared in the same manner as in Example 1-1, but using a different content of the nano-silica surface-treated with organosilane according to Preparation Example 1, as described in Table 1 below.
[0081] Comparative Examples 1-1 to 1-2
[0082] A polyimide varnish was prepared in the same manner as Example 1-1, except that the nano-silica according to Preparation Comparative Example 1 was used instead of the nano-silica surface-treated with organosilane according to Preparation Example 1, and the content thereof was also different, as described in Table 1 below.
[0083] Comparative Examples 1-3 to 1-4
[0084] A polyimide varnish was prepared in the same manner as in Example 1-1, but using a different content of the nano-silica surface-treated with organosilane according to Preparation Example 1, as described in Table 1 below.
[0085] Table 1 below shows the polyamic acid compositions, solid contents, and the types and contents of nano-silica of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-4.
[0086] [Table 1]
[0087]
[0088] Example 2. Polyimide cured product (polyimide film)
[0089] Example 2-1
[0090] The polyimide varnish prepared according to Example 1-1 was rotated at a high speed of 2,000 rpm to remove bubbles. Then, the degassed polyimide varnish was applied on a glass substrate (230 mm×230 mm, thickness: 0.55 mm) using a spin coater.
[0091] Next, in a nitrogen atmosphere, curing was carried out under the conditions of 110° C. (20 minutes) → 150° C. (20 minutes) → 200° C. (20 minutes) → 300° C. (20 minutes) to obtain a thin film type polyimide cured product (thickness of 20±1.0 μm or 26±1.0 μm).
[0092] Examples 2-2 to 2-7
[0093] Polyimide cured products were prepared in the same manner as in Example 2-1, except that the polyimide varnishes according to Examples 1-2 to 1-7 were respectively used instead of the polyimide varnish according to Example 1-1.
[0094] Comparative Examples 2-1 to 2-4
[0095] Polyimide cured products were prepared in the same manner as in Example 2-1, except that the polyimide varnishes according to Comparative Examples 1-1 to 1-4 were respectively used instead of the polyimide varnish according to Example 1-1.
[0096] Example 3. Polyimide coating material
[0097] Example 3-1
[0098] In a coating curing oven, an electric wire containing a polyimide coating material having a coating thickness of 110±10 μm was prepared by repeating the process of coating, drying and curing the polyimide varnish according to Example 1-1 on a square copper wire 20-28 times.
[0099] Examples 3-2 to 3-7
[0100] Wires containing a polyimide coating material were prepared in the same manner as in Example 3-1, except that the polyimide varnishes according to Examples 1-2 to 1-7 were respectively used instead of the polyimide varnish according to Example 1-1.
[0101] <Experimental Example>
[0102] Experimental Example 1. Comparison of Zeta Potential of Polyimide Varnishes
[0103] The zeta potential of the polyimide varnish obtained according to the embodiment and the comparative example was measured twice by inputting the refractive index, viscosity and dielectric constant of dimethylacetamide into the Benano 180zeta pro instrument of Bettersize, and the average value thereof was obtained by calculating the arithmetic mean. The absolute value of the average value obtained by calculating the arithmetic mean is listed in Table 2 below.
[0104] [Table 2]
[0105]
[0106] According to Table 2, as shown in Comparative Examples 1-1 and 1-2, as the content of nano-silicon dioxide increases, the zeta potential of the varnish generally shows a downward trend. However, it can be confirmed in Examples 1-1 to 1-7 that as the content of nano-silicon dioxide increases, the zeta potential of the varnish shows an upward trend. This shows that the present invention improves dispersibility by using nano-silicon dioxide with a large absolute value of zeta potential, so even if the varnish contains a certain range of high-content nano-silicon dioxide, the zeta potential of the varnish is also very high and will not decrease.
[0107] Experimental Example 2. Evaluation of physical properties of polyimide
[0108] (1) Pulse durability
[0109] The pulse durability was determined according to IEC-60851-5 by attaching the polyimide films (thickness 26±1.0 μm) of the examples and comparative examples to a jig, applying an AC voltage of 1.5 kV (frequency 60 Hz), and measuring the time until a leakage current of 5 mA or more was detected. The results are shown in Table 3 below.
[0110] (2) Haze
[0111] The haze of the polyimide films (thickness: 20±1.0 μm) or varnishes of the examples and comparative examples was measured using HunterLab equipment according to ASTM E308. The results are shown in Table 3 or Table 4 below.
[0112] [Table 3]
[0113]
[0114] [Table 4]
[0115]
[0116] According to Table 3, compared with Comparative Examples 2-1 and 2-2, the polyimide film of the present invention has significantly better pulse durability characteristics by using nano silicon dioxide having a larger absolute value of zeta potential. In addition, Examples 2-1 to 2-7 have significantly improved pulse durability characteristics by containing 6 to 20wt% of nano silicon dioxide relative to the solid content of polyimide, but the content of nano silicon dioxide in Comparative Examples 2-3 and 2-4 is not within the above range, and the pulse durability characteristics are very low, less than 300 minutes, or cannot be measured due to the lack of film formation.
[0117] In addition, according to Table 3 and Table 4, all polyimide varnishes and film-type cured products of the present invention can achieve low-level haze characteristics. Specifically, it was confirmed that the haze of the varnishes according to Examples 1-1 to 1-7 was 0.7% or less, and the haze of the films according to Examples 2-1 to 2-7 was 0.8% or less. This shows that the nano-silica is not agglomerated and is uniformly dispersed.
[0118] Therefore, the present invention can maintain the absolute value of the zeta potential of the polyimide varnish at a relatively high level while containing a certain range of high content of nano-silicon dioxide, and also achieve excellent pulse durability and physical properties such as excellent haze.
[0119] The polyimide varnish of the present invention can have excellent physical properties such as excellent haze while having excellent pulse durability by including a certain range of nano-silicon dioxide and satisfying the high absolute value of the zeta potential of the polyimide varnish.
[0120] The present invention can also be used as a conductor coating for windings of electric vehicles (EVs), and has excellent uses.
[0121] In the specification, details that can be fully recognized and inferred by those skilled in the art to which the present invention belongs are omitted. In addition to the specific embodiments described in this specification, various modifications can be made within the scope of not changing the technical spirit or basic structure of the present invention. Therefore, the present invention can be implemented in other ways than those specifically described and exemplified herein, and those skilled in the art can understand this.
Claims
1. A polyimide varnish comprising: polyamic acid and nano-silicon dioxide, wherein the content of the nano-silicon dioxide is 5 to 23 wt % relative to the solid content of the polyamic acid, and the absolute value of the zeta potential of the polyimide varnish is 1 to 30 mV.
2. The polyimide varnish according to claim 1, wherein the nano silicon dioxide is surface-modified with an organosilane.
3. The polyimide varnish according to claim 2, wherein the organosilane of the nano-silica surface-modified with the organosilane comprises one or more selected from the group consisting of: methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styreneethyltrimethoxysilane, Methoxysilane, phenyltriethoxysilane, p-toluenetriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltrimethoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropoxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidyl ether propyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxysilane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES). 4 . The polyimide varnish according to claim 1 , wherein the absolute value of the zeta potential of the nano-silicon dioxide is 10.0 mV to 40.0 mV. The polyimide varnish according to claim 1 , wherein the average particle diameter of the nano-silicon dioxide is 1 to 200 nm. 6 . The polyimide varnish according to claim 1 , wherein the solid content of the polyamic acid is 10 to 50 wt %. 7 . The polyimide varnish according to claim 1 , wherein the polyamic acid contains a dianhydride monomer and a diamine monomer as polymerization units.
8. The polyimide varnish according to claim 7, wherein the dianhydride monomer comprises at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenyl sulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride. 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.
9. The polyimide varnish according to claim 7, wherein the diamine monomer comprises at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenylpropane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-methylenediamine (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-toluidine), 2,2'-bis( trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl) sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diamino Benzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis( 3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-Bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy bis[4-(4-aminophenoxy)phenyl] ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]thioether, bis[4-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane )phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane. 10 . The polyimide varnish according to claim 1 , wherein the polyamic acid contains pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as polymerization units. 11 . The polyimide varnish according to claim 1 , wherein a molar ratio of the dianhydride monomer to the diamine monomer is 6:4 to 4:
6. 12 . The polyimide varnish according to claim 1 , wherein the polyimide varnish further comprises an organic solvent.
13. The polyimide varnish according to claim 11, wherein the organic solvent comprises at least one selected from the group consisting of: N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, gamma-butyrolactone (GBL), diethylene glycol dimethyl ether and naphthalene.
14. The polyimide varnish according to claim 1, wherein the polyimide varnish is molten at a temperature of 30°C and a shear rate of 1 s -1 The viscosity measured is 500 cP to 20,000 cP.
15. The polyimide varnish according to claim 1, wherein the polyimide varnish has a haze of 1.5% or less.
16. A polyimide cured product obtained by curing the polyimide varnish according to claim 1. 17 . The cured polyimide product according to claim 16 , wherein the cured polyimide product is a polyimide film. 18 . The polyimide cured product according to claim 16 , wherein the polyimide cured product has a haze of 1.5% or less.
19. The polyimide cured product according to claim 16, wherein the polyimide cured product has a pulse durability of 300 minutes or more, the pulse durability being the time for an insulating material to withstand a certain voltage according to IEC-60851-5.
20. A polyimide coating material comprising the polyimide varnish according to claim 1.
Citation Information
Patent Citations
Flexible transparent LED touch display film structure that can be detached and partially repaired
KR1020230112846A
Polyimide varnish and preparation method and application thereof
CN109135554A
Novel Saccharomyces cerevisiae strain and use thereof
KR1020230091073A